2019
DOI: 10.1186/s13052-019-0728-5
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis and its outcome following percutaneous closure of cardiac defects among children and adolescents: a prospective study

Abstract: Background Transcatheter closure of intracardiac defects might be complicated by intravascular hemolysis. We evaluated hemolysis and its outcome after transcatheter closure of these defects. Methods and patients All patients who underwent transcatheter closure of patent ductus arteriosus, ventricular septal defect and atrial septal defect were included in this prospective study. Clinical data were obtained before and after the cathet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…Hemolysis can occur with or without residual shunts following PDA device closure. Amoozgar et al [ 15 ] reported four cases of hemolysis out of total 138 cases following device closure of left to right shunts. Mortality of surgical PDA ligation has been reported to be as high as 2% in one study [ 16 ] while mortality from trans-catheter PDA closure is low.…”
Section: Discussionmentioning
confidence: 99%
“…Hemolysis can occur with or without residual shunts following PDA device closure. Amoozgar et al [ 15 ] reported four cases of hemolysis out of total 138 cases following device closure of left to right shunts. Mortality of surgical PDA ligation has been reported to be as high as 2% in one study [ 16 ] while mortality from trans-catheter PDA closure is low.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the initial residual forward flow through the device, the patient was regularly followed up with echocardiography ( Figure 4 , Video 4 ) and monitored for signs of hemolysis. 2 He had preliminary evidence of hematuria on urinalysis and raised lactate dehydrogenase levels. This was managed conservatively and resolved within 3 weeks.…”
Section: Managementmentioning
confidence: 99%
“…El cierre del defecto del tabique interventricular mediante técnica percutánea, puede generar hemólisis, fundamentalmente debido a un cortocircuito residual o a una exposición mecánica del dispositivo de cierre al flujo sanguíneo que habitualmente no precisa de la retirada ni recambio del dispositivo y, según las series de casos, aparece entre un 0,7 y un 15% de los casos 24 .…”
Section: Cierre Percutáneounclassified
“…El listado definitivo de desenlaces con los que se ha trabajado en el presente informe se pueden ver en la tabla 6. Anexo Amoozgar et al 2019 24 Desenlaces sin interés para la pregunta de investigación.…”
Section: Los Criterios Empleados Fueron Los Siguientesunclassified